+0  
 
+1
96
2
avatar+91 

Simplify the expression. 

 Dec 19, 2018

Best Answer 

 #2
avatar+98044 
+1

( -5 + i ) * i         -5i + i^2           -5i - 1          - (5i + 1)        5i + 1

_________ =    _______  =   ________ =  _______   =   _______

   2i * i                  2i^2               -2                   -2                    2

 

 

 

cool cool cool

 Dec 19, 2018
 #1
avatar+17231 
+2

Multiply top and bottom by  -2i

 

(-5+ i )/ 2i   *  -2i/-2i =     -10i  - 2i^2   /  -4i^2      =  ( 2 - 10 i ) / 4  =   ( 1-5i)  / 2

 

(NOTE:  You COULD have just multiplied top and bottom by  -i  to get same result )  

 Dec 19, 2018
 #2
avatar+98044 
+1
Best Answer

( -5 + i ) * i         -5i + i^2           -5i - 1          - (5i + 1)        5i + 1

_________ =    _______  =   ________ =  _______   =   _______

   2i * i                  2i^2               -2                   -2                    2

 

 

 

cool cool cool

CPhill Dec 19, 2018

29 Online Users

avatar
avatar
avatar
avatar